Correlates of domestic violence in the urban slum of North Bengal, India - Kuntala Ray; Hironmoy Roy; Manasi Chakraborty (Al Ameen Medical College, 2020)
Background: Domestic Violence is a social curse prevalent since long time back. Changing socioeconomic scenario due to globalization, urbanization and changing behaviour, might keep its impact on the magnitude of domestic violence. Objective: To determine the pattern of Domestic Violence among the women of reproductive age group (15-44 years) in the urban area of Siliguri and to find-out the determinants associated in relation to Domestic Violence. Method: A community based descriptive cross-sectional study was conducted from June 2013 - May 2014 in a urban slum of Siliguri among the women of reproductive age (15-45 yrs) who were permanent resident of that area with a pretested, predesigned, structured schedule prepared with the guidance from NFHS-3 questionnaire and applied on total 284 respondents who consented to participate. Result: 'Physical violence' was found to be correlated with "age", "caste" of the women, "husbands' literacy status" as well as "husband's addiction to alcohol"; whereas the 'sexual violence' was associated with "age of the women", "literacy level of the couple" "child's gender" and "husband's addiction". Emotional violence was associated with "child's gender" and "marriage-duration". Spousal 'controlling behaviour' was found to be significantly associated with "gender of the child" and "duration of marriage". Conclusion: This search for the pattern of domestic violence as well as its different determinants is expected to be helpful for future policy making and awareness programme.